The IkappaB kinase family phosphorylates the Parkinson's disease kinase LRRK2 at Ser935 and Ser910 during Toll-like receptor signaling. - Nicolas Dzamko (Public Library of Science (PLoS), 2012)
Mutations in leucine-rich repeat kinase 2 (LRRK2) are strongly associated with late-onset autosomal dominant Parkinson's disease. LRRK2 is highly expressed in immune cells and recent work points towards a link between LRRK2 and innate immunity. Here we demonstrate that stimulation of the Toll-Like Receptor (TLR) pathway by MyD88-dependent agonists in bone marrow-derived macrophages (BMDMs) or RAW264.7 macrophages induces marked phosphorylation of LRRK2 at Ser910 and Ser935, the phosphorylation sites that regulate the binding of 14-3-3 to LRRK2. Phosphorylation of these residues is prevented by knock-out of MyD88 in BMDMs, but not the alternative TLR adaptor protein TRIF. Utilising both pharmacological inhibitors, including a new TAK1 inhibitor, NG25, and genetic models, we provide evidence that both the canonical (IKKα and IKKβ) and IKK-related (IKKε and TBK1) kinases mediate TLR agonist induced phosphorylation of LRRK2 in vivo. Moreover, all four IKK members directly phosphorylate LRRK2 at Ser910 and Ser935 in vitro. Consistent with previous work describing Ser910 and Ser935 as pharmacodynamic biomarkers of LRRK2 activity, we find that the TLR independent basal phosphorylation of LRRK2 at Ser910 and Ser935 is abolished following treatment of macrophages with LRRK2 kinase inhibitors. However, the increased phosphorylation of Ser910 and Ser935 induced by activation of the MyD88 pathway is insensitive to LRRK2 kinase inhibitors. Finally, employing LRRK2-deficient BMDMs, we present data indicating that LRRK2 does not play a major role in regulating the secretion of inflammatory cytokines induced by activation of the MyD88 pathway. Our findings provide the first direct link between LRRK2 and the IKKs that mediate many immune responses. Further work is required to uncover the physiological roles that phosphorylation of LRRK2 by IKKs play in controlling macrophage biology and to determine how phosphorylation of LRRK2 by IKKs impacts upon the use of Ser910 and Ser935 as pharmacodynamic biomarkers.